A Novel Deployable Open Ends Support Reflector - Adnan D. Mohammed; Adnan D. Mohammed; Muhsin J. Jweeg (Engineering and Technology Journal, 2008)
This paper presents an improved deployable reflector concept for an Earthobservation mission that requires a low-cost L-band Synthetic Aperture Radar(SAR) satellite. The required reflector shape is an offset parabolic cylinder with anarc length of 7.888 m and a width of 3.2 m. A novel hollow solid structuralconcept is proposed that comprises curved surfaces formed from thin sheets ofcarbon-fiber-reinforced-plastic (CFRP) connected by flexible hinges along theedges. This proposed structure has very high stiffness-to-weight-ratio, because ofits thin-walled box-type construction. A preliminary design of the full-scalestructure in deployed configuration, which has an estimated mass 22.5 kg and18.665 kg and fundamental natural frequency of 0.72 Hz and 0.64 Hz before andafter the optimization analysis respectively, is presented in the paper. This is 3.5 to4.2 times lighter than the traditional reflector structure, made from lightweightcurved panels with self-locking hinges. A detailed study of a quarter-scaletechnology demonstrator made of 0.6mm thick thermoplastic (nylon), includingdesign, manufacture and testing is also presented.